Penerapan Model Multiliterasi dakam Pembelajaran Teks Prosedur di Kelas 6 Sekolah Dasar - Alifia Marsha Dina; Belinda Dewi Regina; Abdurrohman Muzzaki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Language is a means of knowledge and competence that is very important to be mastered in forming language skills in reading ability, but in reality at SD Tlekung 02 it has been found that reading comprehension ability is still very low, it can be proven through the results of the cycle test with success reaching 35% of students who have completed it, therefore the purpose of this study is to improve the reading comprehension ability of grade 6 elementary school students at SDN Junrejo 01 Batu City by applying the multiliteracy model through procedural texts. The method used is PTK (Classroom Action Research). This research model is a research model used by Arikunto which was carried out 4 times through techniques consisting of planning, observation, implementation, reflection obtained, namely to show the level of reading comprehension of grade 6 students in procedural texts. The results of the study in cycle I had a score of 67.5. While the score obtained in cycle II was 91. It can be concluded that there has been a significant increase. Therefore it can be concluded that the multiliteracy model can be applied to Indonesian language learning, namely in procedural text material.